Twin Pregnancies in Dairy Cattle: Observations in a Large Herd of Holstein-Friesian Dairy Cows - López-Gatius, Fernando (Animals (Basel), 2020)
SIMPLE SUMMARY: Cows have two ovaries, two uterine horns, two oviducts, and a uterine body. Although they are commonly monovular, they can sustain twin or other multiple pregnancies to term. In cows with a single pregnancy, the embryo implants in the uterine horn that is on the side of ovulation where a corpus luteum develops. Multiple pregnancies are classified into bilateral (one or more embryos in each uterine horn) and unilateral (all embryos in the same uterine horn, right or left) and, in both cases, embryos occur on the side of their corresponding corpus luteum or corpora lutea. Multiple pregnancies are undesirable in dairy herds as they compromise the reproductive performance and productive lifespan of cows. The present study sought to: (a) gain information on the incidence of twin pregnancies, (b) assess and expand information on the relative incidence of bilateral twins compared to unilateral twins, (c) confirm corresponding laterality between embryos and corpora lutea, (d) tabulate the frequency of triplets or quadruplets, and (e) evaluate possible effects of environmental heat stress conditions on the incidence of multiple pregnancies. The data for this study were derived from the ultrasonographic examination of 1130 cows carrying twins, triplets, or quadruplets, and 3160 cows carrying singletons. ABSTRACT: Multiple pregnancies have devastating consequences on the herd economy of dairy cattle. This observational study examines incidence patterns based on data from the ultrasonographic examination of 1130 multiple pregnancies in cows in their third lactation or more carrying twins (98.8%), triplets (1.1%), or quadruplets (0.08%), and 3160 of their peers carrying singletons. Cows became pregnant following a spontaneous estrus with no previous hormone treatments. Irrespective of a significant decrease (p < 0.0001) in the conception rate (28–34 days post-insemination) during the warm period of the year, the multiple pregnancy rate was similar for both warm (26.5%) and cool (26.3%) periods. The incidence of unilateral multiple pregnancies (all embryos in the same uterine horn) was higher than that of bilateral pregnancies (at least one embryo in each uterine horn): 54.4% versus 45.6% (p < 0.0001). This difference rose to 17% during the warm season (p = 0.03). Pregnancy was monitored in unilateral multiple pregnancies until abortion or parturition (n = 615). In the warm period, the parturition rate was 43% compared to 61% recorded in the cool period (p < 0.0001). Thus, a warm climate is the main factor compromising the fate of multiple pregnancies. Some clinical suggestions are provided.